Analisis Pengaruh Citra Merek, Kualitas Produk Dan Kualitas Layanan Terhadap Minat Beli Konsumen Pada Brand Bakso Alex (Studi Pada Konsumen Bakso Alex di Surakarta) - Hidayat, Muhammad Nur, Dr Edi Purwo Saputro, S.E.,M.Si (2017)
Presentation of the study aims to determine the effect image review brands, products and quality service quality customer against buying interest Bakso Alex products. article search by Google using test data analysis method that the validity, reliability and hypotheses for a review Seeing how big influence buying interest consumer product of Bakso Alex. Data used hearts research presentation is a primary data dissemination the form of questionnaire respondents consumers at 100 Bakso Alex. The source data is based on the findings of the questionnaire processing through SPSS. Data analysis techniques used that is the test of validity with all the variables declared invalid value corrected item-total correlation of each variable above 0,195, with reliability test results singer research testing each variable is declared reliable with Cronbach Alpha above 0,600. By criteria that buying interest consumers well as variable image of brand, product and quality service quality positive value and influence on consumer buying interest, hypothesis testing through t test brand image variable on quality service quality products and significant. Test F on each of the variables significantly influence operates commercial test article R2 of 62.2% and the rest of her is explained by variables lie at 37.8%.